Exploring postcolonial relationships within policy transfer: the case of learner-centred pedagogy in Ghana - Sakata, N.; Okrah, A.K.; Yates, C.; Edjah, H. (Comparative Education, 2023)
Framed by Homi Bhabha’s concepts of hybridity and the third space. of enunciation, This study explores postcolonial relationships conceivably enacted through policy borrowing processes of learner-centred pedagogy (LCP) in Ghana. Nine Ghanaian and nine foreign stakeholders were interviewed. Conscious of the power imbalance implicit in traditional aid, the case project attempted to challenge the asymmetrical power relationships by allocating policy leadership and responsibility to Ghanaian stakeholders. However, the third space of enunciation created within the project, it did not seem to lead to a hybridization of pedagogical ideas: while it was the Ghanaians themselves who promoted LCP within the project, the conceptual basis of the reform was dependent on knowledge and experiences, which they gained in the West. This article concludes that the postcolonial turn through hybridization of indigenous and Western pedagogies was not observed, although hybridity may happen in the process of actualizing LCP at school and in the classroom levels.
Research Article
Keywords: Postcolonial theory; pedagogical reform; teacher education reform